Дослідження дозвіллєвої діяльності та фізичної активності молодших школярів у Петерфівському мікрорегіоні - Чегіль Аніко; Csehil Anikó; Aniko Chehil; Пелешкей Емілія; Peleshkei Emilia (Видавництво «Код», 2025)
Резюме. Метою статті є виявлення особливостей дозвіллєвої діяльності та рівня фізичної активності молодших школярів Петрівського мікрорегіону на тлі цифровізації та змін освітніх практик. Результати засвідчили: більшість дітей мають 3–4 год вільного часу у будні, частка пасивного дозвілля (екрани) висока; водночас поширені ігри на подвір’ї, велопрогулянки, футбол. Виявлено обмежену пропозицію секцій у школі/за місцем проживання та недостатню участь батьків у спільних активностях. Отримані дані обґрунтовують потребу у розширенні доступних форм рухової активності, підсиленні ролі школи і сім’ї та цілеспрямованих програмах здоров’язбереження.

Abstract. The aim of this article is to identify the characteristics of leisure activities and the level of physical activity among primary school children in the Peterfalva microregion against the backdrop of digitalization and shifts in educational practices. The study was conducted in spring 2025 across 8 schools in the Berehove district (n = 57; 29 girls, 28 boys), using a questionnaire (26 items, closed and open) and physical fitness tests: 30-m sprint, flexibility, push-ups, 4×9-m shuttle run, standing long jump, and long-distance run without timekeeping. The findings show that most children have 3–4 hours of free time on weekdays, with a high share of screen-based leisure; at the same time, yard games, cycling, and football are common. On fitness tests, the majority meet or exceed age norms; better scores are observed among those attending sports clubs or engaging in active leisure. Limited availability of clubs at school/in the community and insufficient parental participation in joint activities were identified. The results justify the need to expand accessible forms of physical activity, strengthen the roles of school and family, and implement targeted health-promoting programs. The results of the study show that more and more children spend their free time in front of screens, using their phones or watching TV, which can have harmful consequences in the long term. Therefore, a rational and balanced use of free time is an important challenge for modern children. The study found that parents play a key role in shaping children’s attitudes towards movement and sports. They could contribute to this through joint activities - games, walks, hikes. However, the data obtained showed that most parents rarely devote time to such activities, although they try to fulfill this role. In general, it can be stated that the family has a significant influence on the formation of habits in spending free time. Based on generalized data and questionnaires, it was found that students who regularly attend training sessions in or outside of school, as a rule, demonstrate better results. Already in the short term, the effect of regular and purposeful development of physical qualities is manifested. At the same time, it is also obvious that children who actively spend their free time – cycling, playing football or engaging in other physical activities – are also capable of achieving high results. This confirms the need to create more opportunities for them to engage in sports both in school and outside of it.
Study of leisure activities and physical activity of primary school children in the Peterfalva microregion
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-14
Keywords: дозвілля; фізична активність; молодші школярі; Петрівський мікрорегіон; секції; екранний час; здоров’язбереження